Climate Change and Dairy Farming in East Africa: Challenges, Adaptation Strategies, and Pathways to Sustainability - Gitau, Kevin; Cramer, Laura K. (International Livestock Research Institute, 2025)
Dairy farming in East Africa faces increasing risks from climate change, including rising temperatures, erratic rainfall, and more frequent droughts, which are projected to reduce milk yields by up to 35% by 2071–2100 if no action is taken. The dairy sector in East Africa contributes to climate change, particularly through methane (CH4) emissions from livestock enteric fermentation and both methane (CH4) and nitrous oxide (N2O) emissions from manure. A range of adaptation and mitigation strategies are available to enhance livestock resilience to climate stressors and reduce emissions. They include promotion of heat-tolerant breeds, conserving water, improving feed and manure management, and adopting agroforestry. Aligning dairy sector adaptation and mitigation efforts with national and regional climate policy frameworks is essential for achieving climate targets in East Africa. Overcoming barriers to the adoption of adaptation and mitigation measures—such as financial limitations, technical gaps, and weak infrastructure—requires targeted policies, coordinated capacity building, and a multi-stakeholder approach.